Keterbukaan Komunikasi Penderita HIV/AIDS (ODHA) Terhadap Keluarga - Tivany Okta Dhaniswar; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Disclosing about the status of PLWHs needs to be done to get support in order to survive. There is a lot of bad stigma about HIV/AIDS, causing PLWHs to feel anxious about revealing their status. The family has a function as a protector and supporter of each member. Unfortunately, there are still many families who cannot accept the existence of PLWHs so that it can strain the relationship between them. In disclosing or concealing their status, PLWHs need to consider several criteria and strategies to gain acceptance from their families. This study aims to determine the strategies used by PLWHs in revealing or hiding their status and gaining acceptance from their families and the obstacles they experience. This study uses Privacy Communication Management theory by Sandra Petonio and Social Penetration theory by Irwin Altman & Dalmas Taylor as a theoretical framework. This study uses qualitative content analysis with a phenomenological approach. The data collection method used was in-depth interview, with a total of 3 informants who were PLWHs in Semarang who had already made disclosures and had good relations with their families. The results showed that there were several criteria and strategies used in revealing and hiding status and obtaining acceptance from the family. The criteria used are gender, culture, contextual, motivation, and risk-benefit. The strategies used are selecting people and sharing information, shifting the topic of discussion, providing education, and arguing. Different criteria and strategies are used according to the relationship between PLWHs and each family member. In addition, some informants managed to go through all stages of social penetration, where openness and acceptance from the family can create a closer/intimate relationship.